PEREMPUAN INDONESIA TAHUN 1970-an DAN 1980-an DALAM CERPEN KARYA DJUMRI OBENG - Mustikawati, Aquari (Universitas Pendidikan Indonesia, 2018)
This study aims to illustrate the image of Indonesian women in the 1970s and 1980s in three short stories by Djumri Obeng,